DIMENSI SEJARAH DALAM NOVEL MEGAT KARYA RIDA K LIAMSI : KAJIAN INTERTEKSTUAL - Yumna Eltias; Syafrial '; Elmustian ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : Background to this study was to differ from the expression that no text was born without the emptiness of history and culture. The problem that arises is how the historical dimension of the novel Megat Rida K Liamsi works. The purpose of this document on the dimensions of the historical novel Rida K Liamsi Megat works by joining the historical literary lineage Tufat Al Nafis and Al Salatin used to learn textual study. The benefits of this research are divided into three theoretical, practical and educational. The operational definition of the dimensions of the motifs of history is the history that was born in the last lineage. Al Salatin and Tufat Al Nafis with literary texts are born in this time the Megat novel. The data source of this research is the novel Megat, Tufat Al Nafis and Al Salatin family tree. The research data is the text you do not have about the motives of history, which are grouped into categories of intertextual denial, confirmation and inovasi. Methodology is a qualitative method that illustrates the descriptive data. The collection of data used techniques is literature. Validity of data involving triangulation techniques using two validators. Based on the data analysis that is done, it is given that 132 historical motifs of the Megat novel, consisting of 3 types of intertextual denial, as much as six of the data, as much as 50 data confirmation and innovation as much as 76 data.Key Words: The dimensions of history, the novel megat